2011
DOI: 10.1177/1555343411399070
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Human-Robot Interaction in a Military Multitasking Environment

Abstract: A military vehicle crew station environment was simulated and a series of three experiments was conducted to examine the workload and performance of the combined position of the gunner and robotics operator in a multitasking environment. The study also evaluated whether aided target recognition (AiTR) capabilities (delivered through tactile and/or visual cuing) for the gunnery task might benefit the concurrent robotics and communication tasks and how the concurrent task performance might be affected when the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Finally, the current study shows that individual differences such as spatial ability and attentional control can have a profound impact on operator's task performance. Training programs (e.g., attention management) and/or user interface designs (e.g., multimodal cueing displays) should be developed to mitigate performance shortfalls of those with lower spatial ability and attentional control [32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study shows that individual differences such as spatial ability and attentional control can have a profound impact on operator's task performance. Training programs (e.g., attention management) and/or user interface designs (e.g., multimodal cueing displays) should be developed to mitigate performance shortfalls of those with lower spatial ability and attentional control [32].…”
Section: Discussionmentioning
confidence: 99%
“…[4] tasked participants with investigating a pseudo-bomb threat with either a human or robot teammate and found that participants rated their workload as lower when they worked with a robot teammate as opposed to a human. In a similar vein, [2] investigated how multitasking affected a human teammate's reliance on the automation of a robot teammate in a target recognition task and found that participants' attentional control (ability to shift attention flexibly) was a significant factor in task success.…”
Section: Introductionmentioning
confidence: 97%
“…Many advancements have been made to overcome performance issues with regard to robot teleoperation to improve processes such as robot responsiveness and camera video bandwidth (Chen et al, 2007). In addition, further advances in technology and artificial intelligence bring more autonomous capabilities, including enhanced perception and object recognition to situation assessment and decisionmaking (Barnes et al, 2014;Schuster et al, 2013), multi-robot multioperator scenarios (Chen and Barnes, in press;Fincannon et al, 2011), individual differences (Chen, 2011), human-robot trust issues (Hancock et al, 2011), supervisory control (Chen and Barnes, 2012;Chen et al, 2011), and multimodal/bidirectional communications (Lackey et al, 2011), to better support more autonomous robots. As robots become more autonomous, their participation in combat situations expands.…”
Section: Introductionmentioning
confidence: 99%